Numerical simulation of SIC processes: A characterization tool for the design of epitaxial structures in electronics - Pons, Michel; Nishizawa, Shin-Ichi; Wellmann, Peter; Ucar, M.; Blanquet, E.; Dedulle, J.M.; Baillet, F.; Chaussende, D.; Bernard, C.; Madar, R. (ECS Transactions, 2005)
Modeling and simulation of the SiC growth processes, Physical Vapor Transport (PVT) and Chemical Vapor Deposition (CVD), are sufficiently mature to be used as a training tool for engineers as well as a growth machine design tool, e.g. when building new process equipment or up-scaling old ones. It is possible to simulate accurately temperature and deposition distributions, as well as doping. The key of success would be the combined use of simulation, experiments and characterization in a "daily interaction". The different presented examples have the aim to show that this approach has the potential of a characterization tool which could be of great importance in the optimization of epitaxial structures used for the fabrication of SiC-based devices.
Keywords: SiC growth; modeling; simulation